CRIMINAL INVESTIGATION IN ALLEN ESKENS’ NOVEL THE LIFE WE BURY - Suci Amalia; Safitri Hariani (Universitas Islam Sumatera Utara, 2020)
This research is concerned with the criminal investigation done by the protagonist by the name of Joe Talbert in Allen Eskens’s novel entitled The Life We Bury. It aims to reveal Joe Talbert’s investigation on a criminal case to uncover the truth. The novel, books, journals and website relating to the criminal case are used as source of data. The data is analyzed by classifying the obtained data in two sub chapters related to the research problems of this study. The writers adopt the theory from Taber K (2006). They are the protagonist’s way in doing his criminal investigation and the results of his criminal investigation. This research uses descriptive qualitative method in analyzing the data. The finding shows that firstly there are two ways in getting information on the criminal investigation, such as doing inspection in the court of law and doing interview, and secondly that the results of his criminal investigation shows the truth of Carl’s real life and the real murderer.